Hemodynamic Performance of Sutureless vs. Conventional Bioprostheses for Aortic Valve Replacement: The 1-Year Core-Lab Results of the Randomized PERSIST-AVR Trial - Fischlein, Theodor; Caporali, Elena; Asch, Federico M.; Vogt, Ferdinand; Pollari, Francesco; Folliguet, Thierry; Kappert, Utz; Meuris, Bart; Shrestha, Malakh L.; Roselli, Eric E.; Bonaros, Nikolaos; Fabre, Olivier; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objective Sutureless aortic valves are an effective option for aortic valve replacement (AVR) showing non-inferiority to standard stented aortic valves for major cardiovascular and cerebral events at 1-year. We report the 1-year hemodynamic performance of the sutureless prostheses compared with standard aortic valves, assessed by a dedicated echocardiographic core lab. Methods Perceval Sutureless Implant vs. Standard Aortic Valve Replacement (PERSIST-AVR) is a prospective, randomized, adaptive, open-label trial. Patients undergoing AVR, as an isolated or combined procedure, were randomized to receive a sutureless [sutureless aortic valve replacement (Su-AVR)] (n = 407) or a stented sutured [surgical AVR (SAVR)] (n = 412) bioprostheses. Site-reported echocardiographic examinations were collected at 1 year. In addition, a subgroup of the trial population (Su-AVR n = 71, SAVR = 82) had a complete echocardiographic examination independently assessed by a Core Lab (MedStar Health Research Institute, Washington D.C., USA) for the evaluation of the hemodynamic performance. Results The site-reported hemodynamic data of stented valves and sutureless valves are stable and comparable during follow-up, showing stable reduction of mean and peak pressure gradients through one-year follow-up (mean: 12.1 ± 6.2 vs. 11.5 ± 4.6 mmHg; peak: 21.3 ± 11.4 vs. 22.0 ± 8.9 mmHg). These results at 1-year are confirmed in the subgroup by the core-lab assessed echocardiogram with an average mean and peak gradient of 12.8 ± 5.7 and 21.5 ± 9.1 mmHg for Su-AVR, and 13.4 ± 7.7 and 23.0 ± 13.0 mmHg for SAVR. The valve effective orifice area was 1.3 ± 0.4 and 1.4 ± 0.4 cm2 at 1-year for Su-AVR and SAVR. These improvements are observed across all valve sizes. At 1-year evaluation, 91.3% (n = 42) of patients in Su-AVR and 82.3% in SAVR (n = 51) groups were free from paravalvular leak (PVL). The rate of mild PVL was 4.3% (n = 2) in Su-AVR and 12.9% (n = 8) in the SAVR group. A similar trend is observed for central leak occurrence in both core-lab assessed echo groups. Conclusion At 1-year of follow-up of a PERSIST-AVR patient sub-group, the study showed comparable hemodynamic performance in the sutureless and the stented-valve groups, confirmed by independent echo core lab. Perceval sutureless prosthesis provides optimal sealing at the annulus with equivalent PVL and central regurgitation extent rates compared to sutured valves. Sutureless valves are therefore a reliable and essential technology within the modern therapeutic possibilities to treat aortic valve disease.